PEMBINAAN PENDIDIKAN KARAKTER - Husaini Husaini (UIN Sumatera Utara Medan, 2014)
There are many interested cases that would be studied by a judgeman. In this case, the role of goverment and the student’s parents as having role of main central education in forming the behavior of students well. A part of society consider that the problem taken by the students caused by globalization era. The fact of globalization make the society forgot about the significant characters of nation. The educational character is the fundamental of nation which has a very important role and should be taught before to the next generation. Moral crisis and character grow ofcourse related to education directly or indirectly. Character crisis that had involved in this country caused by the destruction of people in the socity especially boys and girls which become the cultural collectively. The cultural will become internally getting to the Indonesian people’s feeling and become a character. The character of Indonesian people is determined by the behaviour of Indonesian people itself. The parents and the headmaster or teacher of school is only hopefully the succesful of students academicly that can be measured by the result of his/her prestige or rank, it is not talking about his/her way in teaching. This things orientally forces the student’s parents to their son for studying hard in order to reach the target hopefully. One way to solve the problem alternatifely is by using the educational character. The educational of character combines and improves the activity of informal education area in the family environtment by getting formal education in the school. Many schools and families should be selective in doing the process of education, don’t appear be bored to the students, teacher, and the parents should often attract the studnts or his/her son to study the nature directly. The process of teaching should not be forced but it should be done pleasently, it is not only based on the theory; teaching is not used the docterin way or arrogantly